2011
DOI: 10.1177/0333102411420585
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture versus topiramate in chronic migraine prophylaxis: A randomized clinical trial

Abstract: We suggest that acupuncture could be considered a treatment option for CM patients willing to undergo this prophylactic treatment, even for those patients with medication overuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
96
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 50 publications
2
96
0
5
Order By: Relevance
“…Curiously, this guideline calculates that the anticonvulsant topiramate is twice as good as acupuncture in preventing migraine, even though direct comparisons with drugs favour acupuncture 67…”
Section: Yes—mike Cummingsmentioning
confidence: 99%
“…Curiously, this guideline calculates that the anticonvulsant topiramate is twice as good as acupuncture in preventing migraine, even though direct comparisons with drugs favour acupuncture 67…”
Section: Yes—mike Cummingsmentioning
confidence: 99%
“…최근 다양한 임상 연구를 통해서 침 치료가 관절염 5) , 두통 6) , 요통 7,8) 등의 통증 질환에 우수한 진통효과가 있음이 증명되 고 있으며, 침의 진통기전을 규명하기 위한 기초 연구 또한 중추신경 계를 중심으로 활발하게 이루어지고 있다 [9][10][11][12] .…”
Section: 사암도인침법의 통증 질환 접근법에 대한 고찰unclassified
“…Adverse events occurred in 6% of the acupuncture group and 66% of the topiramate group. 57 In a recent Cochrane analysis of acupuncture for routine care, Linde and colleagues concluded that there is no evidence for an effect of "true" acupuncture over sham interventions. However, after reviewing 22 trials of 4419 participants with migraine, they concluded that migraine patients can benefit from acupuncture.…”
Section: Acupuncturementioning
confidence: 99%